Cystic Fibrosis with Severe Anaemia and Hypoproteinaemia - Siddique, Md Abu Bakkar; Khan, Kalimuddin; Bera, Aparajita; Ghorai, Sudipta; Mallik, Jasmine; Sarkar, Suman (Journal of Nepal Paediatric Society, 2019)
The presentation of cystic fibrosis (CF) is dependent upon which organs are affected. Severe anaemia is reported to occur rarely in patients with CF. We are presenting a case of 2 months old infant admitted with anaemia, malnutrition, hypoproteinaemia and hypoalbuminaemia, without any pulmonary symptoms at the initial presentation. Abnormal sweat chlorides and low faecal elastase level confirmed the diagnosis of CF. Respiratory symptoms and signs developed later on further follow up.